Simulacra and Hyperreality in Lorcan Finnegan's Vivarium (2019) - Kusuma Wardani, Larasati Dinda (Universitas Negeri Surabaya, 2023)
The study examined Vivarium (2019), a film directed by Lorcan Finnegan, through the framework of Jean Baudrillard's simulacra and simulation notions. This dystopian sci-fi film cleverly incorporates societal commentary. The main goal was to reveal the representation of simulacra and hyperreality in the tale. The research uncovered three orders of simulacra, effectively transforming the Yonder estate into a virtual world. The first order shows startling similarities between the'real' world and the